Contributions of PIBID in the initial training: intersections with points of views of undergraduates in Biology - Mattana, Stéfani Dutra; Zanovello, Regiane; Theisen, Geovane Rafael; Moresco, Terimar Ruoso; Garlet, Tânea Maria Bisognin (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The present work describes perception of students Program Institutional Scholarship Initiation to Teaching about the contribution of the project in initial academic degree in Biological Sciences. For this training perspective to materialize students of PIBID performed in the course of two years various activities of an experimental who ran the school based on the reproduction of concepts and seek with it, constitute a new profile educator. It is the consolidation of this new teaching profile that students of PIBID demonstrated their opinions in an opening question of the impact of the activities of PIBID in your training. The conceptions of academic evidence that the project enables its students to reflect that teaching needs innovative ways to bridge the knowledge and it is this articulation that the PIBID operates, redirecting the teacher looking for new perspectives and encouraging a formation more solid and investigative and these future teachers of biology.